EFFECTIVENESS OF RECOMMENDED CLIMATE SMART AGRICULTURE (CSA) PRACTICES IN TELANGANA STATE - A.D. SAILAJA; K. SUPRIYA, C. YUVARAJ, I. SREENIVASA RAO, K. RAVI SHANKAR, G. SREENIVAS (The Journal of Research, PJTSAU, 2023)
Climate change has become a global concern demanding attention and action. In a densely populated country like India, particularly the effects of climate change are more detrimental due to its highly vulnerable nature. In view of the increased importance to address the development needs of the farmers, Indian Council of Agricultural Research (ICAR) has launched various projects and programmes to cope with climatic changes by disseminating the climate resilient and smart agricultural technologies. The study was conducted to identify the effectiveness of various recommended Climate Smart Agriculture (CSA) practices to understand the extent to which these technologies are effective and their capability of decreasing the vulnerability of agriculture and subsequent beneficial nature in the long run. The analysis of climatic variability of the Telangana during the study period revealed that the recent decade (2008-2017) has shown the highest variation in annual rainfall (CV= 29.03%) and mean maximum temperature (CV = 2.38 %) compared to the past two decades. The recent decade (2008-2017) has seen a steady increase in the seasonal rainfall across all the months compared to the earlier decade (1998-2007). Ex-post facto research design was followed and 300 respondents selected by using random sampling method. The analysis of effectiveness of CSA practices perceived by the farmers revealed that majority were found to have medium economic efficiency (44.3%) followed by high (34.3%) and low (21.3%) economic efficiency. The possible reason might be attributed due to sub division and fragmentation of the farm size resulting in enhancing ofsmall and marginal land holdings. It may not be feasible to take up all the CSA practices in these holdings. Most of the farmers are not inclined to be in touch with the changes in environmental climate change, this trend may be due to the idiosyncratic behaviour established by the virtue of their medium to old age, less education and possessing low degree of other profile characteristics and majority of them seemed to be not following the Weather Based Agro Advisory Services (WBAAS) regularly as they were taking up the farm activities naturally which limits the effectiveness of CSA practices at critical periods of time.